Awareness of Listeria and high-risk food consumption behavior among pregnant women in Louisiana. (June 2017) - Xu, Wenqing; Cater, Melissa; Gaitan, Adriana; Drewery, Merritt; Gravois, Rebecca; Lammi-Keefe, Carol J.
Abstract: Listeria monocytogenes is transmitted predominantly through contaminated food. About one in seven (14%) cases of Listeria infection occurs during pregnancy. In this study, we assessed the awareness of foodborne pathogens including Listeria and high-risk food consumption, among 218 pregnant women in southeastern Louisiana parishes in and around an urbanized area. The results showed the relationship between awareness of Listeria and selected demographic variables, such as age, race, and education level. The majority (71.1%) of pregnant women reported the consumption of high-risk foods during pregnancy. One person reportedly consumed six of the seven high-risk foods. Gaps existed between awareness of Listeria and high-risk food consumption behaviors, although as pregnant women's awareness of Listeria increased, their high-risk food consumption behaviors decreased. Targeted continuing education for pregnant women in Louisiana should address the gaps identified in this study. Highlights: Majority of pregnant women in southeastern Louisiana were aware of Listeria. Correlations existed between awareness of Listeria and demographic variables. Majority of pregnant women reported the consumption of high-risk foods. Gaps existed between Listeria awareness and high risk food consumption behavior.